Brincando com o som da bandinha - Verão, Silvana Pedrosa; Bernardo, Lucia Valério da Silva; Gonçalves, Rosicler da Silva (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf